Bułgarsko-polskie paralele w rozwoju systemu fonetycznego - wymowa spółgłoski [ł] = Bulgarian-Polish parallels in the development of phonetic system: The pronunciation of the consonant [ł] - Ałbuł, Olha; Soroka, Olha (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article examines a very interesting process in the Bulgarian phonetic system, i.e. changes in the articulation of the alveolar-dental consonant [l] as [ł]. The comparative study shows that a similar process has taken place in the Polish language, leading to changes in its consonantal system.
Keywords: język bułgarski; język polski; spółgłoska [ł]; Bulgarian language; Polish language; consonant [ł]